Organometallic halogen bond acceptors: directionality, hybrid cocrystal precipitation, and blueshifted CO ligand vibrational band. Issue 16 (20th March 2018) - Torubaev, Yury V.; Skabitskiy, Ivan V.; Rusina, Polina; Pasynskii, Alexander A.; Rai, Dhirendra K.; Singh, Ajeet
Abstract : The halogen bonding (XB) in metal carbonyls blueshifts the ν CO band and XB directionality is dictated by XB-accepting atom hybridization. Abstract : Iron cyclopentadienyl carbonyl-halide and -chalcogenolate complexes CpFe(CO)2 X (X = Cl, Br, I, TePh, SPh) readily afford cocrystals with the bidentate halogen bond donor 1, 4-diiodotetrafluorobenzene ( p -DITFB) under slow evaporation or vapor diffusion conditions. The same microcrystalline [CpFe(CO)2 TePh]( p -DITFB) product instantly precipitates upon mixing p -DITFB and CpFe(CO)2 TePh in hexane solution. Supramolecular [CpFe(CO)2 X( p -DITFB)] n chains in the cocrystals are assembled by halogen bonds (XB) between the electrophilic area of iodine atoms of p -DITFB and the nucleophilic area of X in CpFe(CO) n X. The 5–10 cm −1 hypsochromic shift of the CO stretching bands in the IR spectra of [CpFe(CO)2 X( p -DITFB)] cocrystals is explained by the pronounced electron-withdrawing effect of halogen bonding (XB), as supported by DFT calculations. The observed influence of the nature of the XB acceptor (X) on the XB geometry is described in terms of hybridization and electrostatic surface potential (ESP) mapping.